BENTUK HAK TERSANGKA DALAM HUKUM PIDANA ISLAM - Zumrotul Muthoharoh (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Justice is a value that is highly emphasized in Islam in any case and to anyone, especially in the field of law. The law of all people is the same. Islam does not distinguish class, rank, position, position, family. The rule of law in Islam is absolutely uncompromising, without distinction of descent, religion and so on. Before God there can be no disrimination in law enforcement. Because Islam respects the truth as the glory of man is respected. The original purpose, kuhap placed the suspect/defendant as a subject where in every examination the suspect/defendant must be treated in a position as a human being who has dignity, dignity and dignity. But in practice, often the suspect/defendant is seen as an object that is dated human rights and dignity arbitrarily by law enforcement officials.